1995
DOI: 10.1088/0957-0233/6/7/015
|View full text |Cite
|
Sign up to set email alerts
|

Absolute detection efficiencies of a microchannel plate detector for ions

Abstract: Absolute single-palticle detection efficiencies of a microchannel plate (MCP) detector were determined by photo-ionization of atoms or molecules. The ionized heavy particles were detected in coincidence with the resulting electrons. This method allows the determination of detection efficiencies without a knowledge of the absolute event rates. We obtained the detection efficiencies for the ions H' , D;, H D ' , Ht, Dt and Ar' in the impact energy range 0-5 keV. The detection ekiencies saturate above 3 keV and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…When the ion impact energy is sufficiently high ͑Ͼ3 keV͒ heavy ions and low mass ions are detected with equal detection efficiency. [18][19][20] From this it follows that the signal intensity of ions of different species can be compared. However, because the detection efficiency may differ for particles with different kinetic energies, only the signal of ions with equal energy and E kin Ͼ 3 keV can be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…When the ion impact energy is sufficiently high ͑Ͼ3 keV͒ heavy ions and low mass ions are detected with equal detection efficiency. [18][19][20] From this it follows that the signal intensity of ions of different species can be compared. However, because the detection efficiency may differ for particles with different kinetic energies, only the signal of ions with equal energy and E kin Ͼ 3 keV can be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…13 Moreover, it has been shown that when the ion impact energy is sufficiently high ͑Ͼ3 keV͒, heavy ions are detected with equal efficiency as low mass ions. [14][15][16] This justifies that with the use of the gated MCP, time-resolved images can be made of the ion beam.…”
Section: Methodsmentioning
confidence: 98%
“…The efficiency for the detection of low energy ions (few keV) with a Micro Channel Plate (MCP) is only 30% [12][13][14]. This can be improved by converting the ions into electrons, which are easily detected with up to 90% efficiency (see Fig.…”
Section: Motivation Choice and Description Of The New Detectormentioning
confidence: 99%